Using Dark Energy Explorers and Machine Learning to Enhance the Hobby-Eberly Telescope Dark Energy Experiment - House, Lindsay R.; Gebhardt, Karl; Finkelstein, Keely; Cooper, Erin Mentuch; Davis, Dustin; Ciardullo, Robin; Farrow, Daniel J.; Finkelstein, Steven L.; Gronwall, Caryl; Jeong, Donghui; Johnson, L. Clifton; Liu, Chenxu; et al. (Astrophysical Journal, 2023)
We present analysis using a citizen science campaign to improve the cosmological measures from the Hobby-Eberly Telescope Dark Energy Experiment (HETDEX). The goal of HETDEX is to measure the Hubble expansion rate, H(z), and angular diameter distance, D A(z), at z = 2.4, each to percent-level accuracy. This accuracy is determined primarily from the total number of detected Lyα emitters (LAEs), the false positive rate due to noise, and the contamination due to [O ii] emitting galaxies. This paper presents the citizen science project, Dark Energy Explorers (https://www.zooniverse.org/projects/erinmc/dark-energy-explorers), with the goal of increasing the number of LAEs and decreasing the number of false positives due to noise and the [O ii] galaxies. Initial analysis shows that citizen science is an efficient and effective tool for classification most accurately done by the human eye, especially in combination with unsupervised machine learning. Three aspects from the citizen science campaign that have the most impact are (1) identifying individual problems with detections, (2) providing a clean sample with 100% visual identification above a signal-to-noise cut, and (3) providing labels for machine-learning efforts. Since the end of 2022, Dark Energy Explorers has collected over three and a half million classifications by 11,000 volunteers in over 85 different countries around the world. By incorporating the results of the Dark Energy Explorers, we expect to improve the accuracy on the D A(z) and H(z) parameters at z = 2.″4 by 10%-30%. While the primary goal is to improve on HETDEX, Dark Energy Explorers has already proven to be a uniquely powerful tool for science advancement and increasing accessibility to science worldwide.
Keywords: Cosmology; Cosmological parameters; Astronomy education; Dark energy